Analisis Pengaruh Penambahan Urea Terhadap Pelepasan Air Yang Terserap Oleh Super Absorbent Polymer (SAP) Dalam Popok Sekali Pakai - Fadlilatin Nailah; Millisa, Millisa (Politeknik Negeri Madura, 2023)
The use of disposable diapers is very high these days. The diapers consist of constituent layers, namely the upper layer, acquisition, core, and outer layer. In the core layer there is a main absorbent material called Super Absorbent Polymer (SAP). The use of SAP in the diapers is very much needed. However, currently there is no good management of diaper waste. This causes an imbalance in the environment and will eventually pollute the environment. SAP is widely used in agriculture as a keeper of soil moisture, nutrient carrier, and water storage, especially in dry areas. The use of SAP contained in disposable diapers is still very rare. SAP absorption is very strong, so that the liquid that has been absorbed is very difficult to release again. One way to release absorbed water is by adding urea to water-saturated SAP. Then an analysis was carried out using the DoE program to obtain the optimum value of water that can be released from SAP with the addition of urea. Based on the research that has been done, the optimum value of water released by SAP due to the addition of urea is 70.86 mL/75.13 gr urea. With a data validity value of 85.6%.